2016
DOI: 10.1213/ane.0000000000001244
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Controlled Analgesia Plus Background Opioid Infusion for Postoperative Pain in Children: A Systematic Review and Meta-Analysis of Randomized Trials

Abstract: There was no significant difference in outcomes with the addition of an opioid background infusion to PCA bolus doses of opioid. Further high-quality studies are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Some guidelines advise against the use of a background infusion in adults because of the potential for respiratory depression [ 33 – 35 ]. However, background infusion is widely used in children [ 36 ], who are considered to have a lower risk of respiratory depression [ 37 , 38 ]. A study of the efficacy and safety of PCA in patients with AIS [ 14 ] found no difference between PCA alone and PCA with background infusion with regard to the postoperative use of morphine, side effects, or patient satisfaction and concluded that background infusion did not provide clinically significant advantages over intermittent bolus doses of morphine.…”
Section: Methodsmentioning
confidence: 99%
“…Some guidelines advise against the use of a background infusion in adults because of the potential for respiratory depression [ 33 – 35 ]. However, background infusion is widely used in children [ 36 ], who are considered to have a lower risk of respiratory depression [ 37 , 38 ]. A study of the efficacy and safety of PCA in patients with AIS [ 14 ] found no difference between PCA alone and PCA with background infusion with regard to the postoperative use of morphine, side effects, or patient satisfaction and concluded that background infusion did not provide clinically significant advantages over intermittent bolus doses of morphine.…”
Section: Methodsmentioning
confidence: 99%
“…This finding may be confounded by routine use of continuous respiratory monitoring in the pediatric population . Another meta‐analysis examining randomized controlled studies comparing PCA vs PCA plus background infusion for postoperative children showed no difference in pain scores, opioid consumption, or risk of adverse events at 12 and 24 hours …”
Section: The Use Of Pcamentioning
confidence: 99%
“…PCIA has the advantages of immediately releasing the drug whenever the patient demands in low doses, short intervals, short duration of effect, and easy titration of opioids. Another one is that PCIA can ease of dose titration and adaptability to patients need to analgesics [ 14 ].…”
Section: Discussionmentioning
confidence: 99%